Federal Support for the Development of Speech Synthesis Technologies: A Case Study of the Kurzweil Reading Machine. - Bell, Sarah A. (Information & Culture, 2023)
This case study situates an early text-to-speech computer developed for blind persons, the Kurzweil Reading Machine (KRM), within a broader history of speech synthesis technologies. Though typically no more than a footnote in the technical history of speech synthesis, the KRM was still a powerful symbol of innovation that reveals how disability can be used as a pretext for funding technology development. I argue that various boosters held the KRM up as a symbol of technological solutionism that promised to fully enroll blind people into the US political economy. However, the success of the KRM as a symbol belies its technical flaws, the federal subsidies needed to bring it to fruition, and the structural barriers to its use that were elided by its utopian promise.